Determination of Chlorine in Marine Sediment by Inductively Coupled Plasma-Atomic Emission Spectrometry with Ammonia Extraction - MA Sheng-feng; WEN Hong-li; ZHAO Huai-ying; SUN Hong-bin; GONG Ai-hua (Yankuang ceshi, 2013)
It is difficult to dissociate Cl by plasma because of the high ionization energy. Since the optical path of Inductively Coupled Plasma-Atomic Emission Spectrometry (ICP-AES) cannot produce a low enough vacuum, the light wave of Cl is absorbed intensively causing difficulty in identifying the characteristic spectrum and subsequently in obtaining an accurate measurement of Cl in geology samples. In this article, a method is described here for completely extracting Cl in marine sediment samples by 10% ammonia with 30 minutes ultrasound bath. The Cl was measured by ICP-AES with an analysis spectrum of 725.670 nm. The detection limit of this method, which was based on ten standard deviations of the blank (10σ, dilution factor=100), was 50 μg/g for Cl. The accuracy and precision of the method were verified by analyzing different geological certified reference materials GBW 07313, GBW 07315 and GBW 07316. The relative standard deviations (RSD, n=7) of the results of independent determination GBW 07316 were 4.3%-8.6%, and relative error (n=7) were 2.9%-7.5%. Compared with traditional methods, this method is simple, fast, easy to perform, and its precision and accuracy are suitable for marine geochemistry.